Routledge handbook of politics in Asia - Hua, Shiping (Routledge, Taylor & Francis Group, 2018)
"The Routledge Handbook of Politics in Asia is designed to serve as a comprehensive reference guide to politics in Asia. Covering East, South, Southeast and Central Asia, this Handbook brings together the work of leading international academics to cover the political histories, institutions, economies and cultures of the region. Taking a comparative approach, it is divided in four parts, including: - A thorough introduction to the politics of the four regions of Asia, from the perspectives of democratization, foreign policy, political economy, and political culture. - An examination of the 'Big Three' of Asia: China, India, and Japan, focusing on issues including post-Mao reform, China's new world outlook, Indian democracy and Japanese foreign policy. - A discussion of important contemporary issues such as human rights, the politics of the internet, security, nationalism, and geopolitics. - An analysis of theoretical ideologies and belief systems connected with the politics of the continent, such as Confucianism, Hinduism, socialist constitutionalism and gender norms. As an invaluable and all-inclusive resource, this handbook will be useful for students, scholars, researchers and practitioners of Asian politics and comparative politics. Shiping Hua is Calvin and Helen Lang Distinguished Chair in Asian Studies, Professor of Political Science, and Director of Asian Studies Program at the University of Louisville, USA" --
Enthält 40 Beiträge von 50 Autoren
Tabellen
Register Seite 605-624
Literaturangaben
Literaturhinweise
Keywords: Asia -- Politics and government -- 1945- -- Handbooks, manuals, etc; Asia -- Handbooks, manuals, etc -- Politics and government -- 1945- -- Asia; Asien; China; Indien; Japan; Südasien; Aufsatzsammlung; Politisches Verhalten; Politische Kultur